Improving the Ability of Madrasah Aliyah Mathematics Teachers to Develop HOTS Questions through Training and Mentoring - Toheri Toheri; Arif Muchyidin (Journal of General Education and Humanities, 2025)
This study aims to enhance the ability of Madrasah Aliyah mathematics teachers to develop Higher-Order Thinking Skills (HOTS) questions through training and mentoring. This research employs a qualitative approach with a case study design involving 20 mathematics teachers. Data were collected through questionnaires, observations, and document analysis, then analyzed using thematic and descriptive statistics. The findings indicate that teachers' understanding of HOTS principles, reasoning levels, and question formulation steps after participating in the training significantly improved, with an average increase of 55–70% across key indicators. However, some teachers still struggled to integrate real-world contexts into the HOTS questions they developed. These findings highlight the importance of continuous professional development programs to strengthen teachers' competency in designing HOTS-based assessments. Further research is needed to explore the long-term impact of this training on student learning outcomes.